2017
DOI: 10.1371/journal.pone.0177914
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TauC3 antibody and demonstration of its potential to block tau propagation

Abstract: The spread of neurofibrillary tangle (NFT) pathology through the human brain is a hallmark of Alzheimer’s disease (AD), which is thought to be caused by the propagation of “seeding” competent soluble misfolded tau. “TauC3”, a C-terminally truncated form of tau that is generated by caspase-3 cleavage at D421, has previously been observed in NFTs and has been implicated in tau toxicity. Here we show that TauC3 is found in the seeding competent high molecular weight (HMW) protein fraction of human AD brain. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The presence of tau seeding as measured using the tau Tau RD -P301S-CFP/YFP in vitro biosensor (Holmes et al, 2014 ) has previously shown an association with the presence of tau pathology, both in tau transgenic mice (Holmes et al, 2014 ; DeVos et al, 2017 ) and in human brains (Furman et al, 2017 ; Nicholls et al, 2017 ; Nobuhara et al, 2017 ). Interestingly, tau seeding has also been reported in tissues—both in mice and in human brain lysate—where overt tau pathology has not yet developed or is rare (Holmes et al, 2014 ; Furman et al, 2017 ), suggesting that some amount of tau aggregates exist in a brain region before they accumulate to a point of filling the neuronal somatodendritic compartment and are abundantly detected by tau IHC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of tau seeding as measured using the tau Tau RD -P301S-CFP/YFP in vitro biosensor (Holmes et al, 2014 ) has previously shown an association with the presence of tau pathology, both in tau transgenic mice (Holmes et al, 2014 ; DeVos et al, 2017 ) and in human brains (Furman et al, 2017 ; Nicholls et al, 2017 ; Nobuhara et al, 2017 ). Interestingly, tau seeding has also been reported in tissues—both in mice and in human brain lysate—where overt tau pathology has not yet developed or is rare (Holmes et al, 2014 ; Furman et al, 2017 ), suggesting that some amount of tau aggregates exist in a brain region before they accumulate to a point of filling the neuronal somatodendritic compartment and are abundantly detected by tau IHC.…”
Section: Resultsmentioning
confidence: 99%
“…In keeping with the idea that tau aggregates move across synapses, one possible treatment is tau immunotherapy—as tau aggregates are released from a neuron, the aggregates can be captured by an antibody and cleared before they can be taken up by the adjoining neuron. This therapy has been shown both in vitro and in vivo to be successful at preventing both tau pathology formation and propagation (Boimel et al, 2010 ; Bi et al, 2011 ; Yanamandra et al, 2013 ; Castillo-Carranza et al, 2014 ; Ittner et al, 2015 ; Nicholls et al, 2017 ; Nobuhara et al, 2017 ). Based on these successful studies, tau immunotherapy has been taken to the human clinic by multiple groups for those with early AD (NCT02880956, NCT03289143, NCT03056729).…”
Section: Discussionmentioning
confidence: 99%
“…Proposed mechanisms for tau immunotherapies are epitope, affinity, conformation, and aggregate size dependent. Studies of specific tau immunotherapies have demonstrated that either extracellular ( Yanamandra et al., 2013 ) or intracellular ( Gu et al., 2013 , Nicholls et al., 2017 ) tau can be targeted. Antibodies are thought to halt the progression of disease by binding to tau aggregates, triggering their uptake and clearance via either endosomal or proteasome pathways ( Chai et al., 2011 , Gu et al., 2013 , Mallery et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tau propagation hypothesis, based on the concept that the clinical progression of AD is linked with the spreading of the tau pathology, supports the idea that clearing the tau involved in propagation may slow the spread of the tau pathology and possibly of cognitive decline (Nicholls et al, 2017;Nobuhara et al, 2017). The potential efficacy of antibodybased therapeutics targeting tau has been demonstrated in several studies using animal models Pedersen and Sigurdsson, 2015), although it is unclear how an antibody can exert its therapeutic efficacy against an intracellular protein such as tau.…”
Section: Future Directions: Toward Diagnosis and Treatment Based On Tmentioning
confidence: 96%